Attachment and adaptive skills in children of international adoption. Issue 1 (30th May 2012) - Barcons, Natàlia; Abrines, Neus; Brun, Carme; Sartini, Claudio; Fumadó, Victoria; Marre, Diana
ABSTRACT The attachment pattern of a sample of 168 internationally adopted children was explored in this study using the semi‐structured Friends and Family Interview. The pattern was analysed in relation to the development of adaptive skills as an expression of the children's resilience. The secure attachment pattern rates were slightly lower and the insecure attachment patterns were considerably higher than those of normative samples from the previous studies. The children from Eastern Europe demonstrated a more insecure attachment pattern (odds ratio [OR]= 2.46; confidence interval [CI]= 1.23–3.94), and their scores on the adaptive skills scales were lower than the scores of children from other countries (OR = 2.62; 95% CI = 1.02–6.72). These results help to identify the groups at risk of failing to develop secure attachment patterns and appropriate adaptive skills, and should provide valuable information for designing effective interventions.